PERANCANGAN AUTENTIKASI MULTI FAKTOR DENGAN PENGENALAN WAJAH DAN FIDO (FAST IDENTITY ONLINE) - Atmawijaya, Rizky; Radiyah, Ummu (INTI Nusa Mandiri, 2024)
Digital services based online are assets that need to be safeguarded, especially if the application still uses single-factor authentication vulnerable to cyberattacks and potential data leaks and identity theft. The proposed solution is to implement multi-factor authentication (MFA) utilizing facial recognition, particularly through FaceNet technology. Although facial recognition can provide an additional layer of security, the main challenge is to maintain user privacy even if biometric information might leak. This research aims to create a secure, reliable MFA model that protects the privacy of employees at PT Traspac Makmur Sejahtera. The proposed method involves an MFA system with four factors: knowledge factor (password), biometric factor (facial measurements), ownership factor (OTP) and location factor (optional if facial accuracy is insufficient). The implementation of this MFA model enhances security, reliability, and protects employee privacy. Considering the specific needs of the company, this research can assist the company in monitoring the locations of employees working from home (WFH).